Feasibility of satellite vicarious calibration using HYPERNETS surface reflectances from Gobabeb and Princess Elisabeth Antarctica sites - De Vis, Pieter; Howes, Adam; Vanhellemont, Quinten; Bialek, Agnieszka; Morris, Harry; Sinclair, Morven; Ruddick, Kevin (Frontiers in Remote Sensing, 2024)
The HYPERNETS project developed a new hyperspectral radiometer (HYPSTAR®) integrated in automated networks of water (WATERHYPERNET) and land (LANDHYPERNET) bidirectional reflectance measurements for satellite validation. In this paper, the feasibility of using LANDHYPERNET surface reflectance data for vicarious calibration of multispectral (Sentinel-2 and Landsat 8/9) and hyperspectral (PRISMA) satellites is studied. The pipeline to process bottom of atmosphere (BOA) surface reflectance HYPERNETS data to band-integrated top of atmosphere (TOA) reflectances and compare them to satellite observations is detailed. Two LANDHYPERNET sites are considered in this study: the Gobabeb HYPERNETS site in Namibia (GHNA) and Princess Elizabeth Base in Antarctica (PEAN). 36 near-simultaneous match-ups within 1 hour are found where HYPERNETS and satellite data pass all quality checks. For the Gobabeb HYPERNETS site, agreement to within 5% is found with Sentinel-2 and Landsat 8/9. The differences with PRISMA are smaller than 10%. For the HYPERNETS Antarctica site, there are also a number of match-ups with good agreement to within 5% for Landsat 8/9. The majority show notable disagreement, i.e. HYPERNETS being over 10% different compared to satellite. This is due to small-scale irregularities in the wind-blown snow surface, and their shadows cast by the low sun. A study comparing the HYPERNETS measurements against a bidirectional reflectance distribution function (BRDF) model is recommended. Overall, we confirm data from radiometrically stable HYPERNETS sites with sufficient spatial and angular homogeneity can successfully be used for vicarious calibration purposes.